(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2015)
This paper discusses the notion of God as the only Creator, exploring its main implications for conceptualising the identity and purpose of Islamic architecture. The paper concludes that the concept of God as the Creator represents the core of the Islamic doctrine of tawhid (God's Oneness and Uniqueness) which, in turn, presents Islamic architecture with its identity impressing it by its own mould. Buildings in Islam are conceived and erected only to serve God and the noble purpose of creation instituted by the Creator. Ascribing the terms "creation" and "creators" to human beings should always be conditional and metaphorical, not authentic or unqualified. Just as the Creator cannot become creation, similarly a creation cannot become a creator. Only against this backdrop, the role and objective of man on earth, and all his civilisational undertakings, including architecture, are to be viewed and assessed. The implications of this central Islamic tenet for Islamic architecture are studied under the sub-topics of the identity of Islamic architecture and the role of Islamic decorative arts.